Drosophila model and network pharmacology to explore novel targets and novel active components of chinese traditional medications for treating kidney stones - Shiyu Zhang; Jingnan Zhu; Yingjie Ju; Mingxia Lv; Rongdian Yang; Ying Li; Yaodong Miao; Yiwen Wang (Elsevier, 2023)
Background: Kidney stone disease is a common urological and metabolic disease in the world. Many traditional Chinese medications(TCMs) are considered to be effective in treating kidney stones and are widely used in China as alternative and supplementary methods besides surgery. However, the active compounds and molecular mechanisms of most TCM treatments for this disease are still unclear, which limits their application. Study design: Sodium oxalate that is fed to Drosophila can cause calculi in the Malpighian tube. The effects of many traditional Chinese drugs were identified through this Drosophila kidney stone model. In this project, we used a network pharmacological approach to analyze a list of traditional Chinese drugs, which showed strong therapeutic effects on the kidney stones in Drosophila. Results: Four active ingredients were predicted to have effects on treating kidney stones. It is noteworthy that all ingredients were predicted to target the Androgen Receptor (AR). In the end, we used the Drosophila model again to verify the therapeutic effects of luteolin and quercetin and proved that AR was a possible target for the treatment of kidney stones. Conclusion: This approach of combining the Drosophila model in vivo experiments with network pharmacology provides a new paradigm for studying TCM therapeutic mechanisms and discovering active ingredients.